Green transportation infrastructure materials for Infrastructure Development - Widyatmoko, Iswandaru (Universitas Lambung Mangkurat, 2023)
Green Transportation Infrastructure • Roadway design that integrates transportation functionality and ecological sustainability • An environmental approach is used throughout the planning, design, and the construction • The result is a highway that will benefit transportation, the ecosystem, urban growth, public health and surrounding communities